Development of problem-based learning-based student worksheet to improve mathematical problem solving ability in rows and rows material - Indriani, Ulfa Dwi; Ananda, Rusydi (Desimal: Jurnal Matematika, 2024)
Problem Based Learning is one form of effort to reduce problems in the process of learning mathematics. The model used in the teaching and learning process is in accordance with the demands of mathematics learning and is centered on students. This research has the main objective of developing and designing problem-based LKPD with the aim of improving students' ability to solve mathematical problems on the material of rows and series. The use of the research and development (R&D) model was chosen by researchers in this study. The type of development used in this model is 4D; as stated, 4D itself consists of four stages, namely introduction (define), planning (design), development (develop), and dissemination (disseminate). Problem Based Learning-based LKPD on the material of rows and series developed is feasible to use as teaching material in learning with the acquisition of a validation value of 92.44%, declared practical with a score of 87.44% based on students' responses to student worksheets, and declared effective with student completeness increasing with an N-Gain value of 0.72, including the high category. The increase in students' mathematics learning outcomes on the material of rows and series using Problem Based Learning-based Learner Worksheets shows that there is an increase in the mathematical problem-solving ability of students.